Neonatal presentation of transected sigmoid colon following umbilical cord clamping: Hernia of umbilical cord - Charles Newton Odongo; Felix Oyania; Amandine Godier-Furnemont; Joshua Moro; Martin Situma (Journal of Pediatric Surgery Case Reports, 2023)
The umbilicus is a site of numerous embryopathies involving vessels, urachus, mid gut herniation, anterior abdominal wall defects and congenital cysts. Owing to lack of awareness, umbilical cord hernia (HUC) is often misdiagnosed and underreported, with limited data in the literature. We report an isolated case of congenital HUC and perinatal transection of the sigmoid colon during cord ligature by a midwife in a local health center.A six-day old female neonate presented with discharge of fecal matter through the umbilicus. The clamped cord, became swollen and auto-amputated on day of life three, after which fecal discharge was from the stump was noted. On examination a visible bowel loop containing stool was seen in the umbilical cord. We proceeded with surgical intervention via a small umbilical incision, with findings of transection of the sigmoid colon, no peritoneal contamination, and primary anastomosis was performed. There was event free recovery postoperatively.HUC is poorly understood and often misdiagnosed as omphalocele minor. One should be cognizant of HUC when noting swelling at the base of the cord so as to avoid any inadvertent iatrogenic enterotomy by close umbilical clamping.